The importance of folkloric games in the Iraqi child theatre (Al-Academy, 2017)
The folkloric games widely considered as expressional forms of nations culture and their environment which can be an important element in Iraqi child theatre shows. For its moral and habits relation to the needs of children which present an effective mean to preserve the true identity of the society character and moral. The research concluded many topics considering the importance of folkloric games in the Iraqi child theatre, the first chapter studied the problem , the necessity , the aim of the research to clarify the importance of folkloric games in Iraqi child theatre, the second chapter is the theoretical part of the research that studied the concept of folkloric games and its implementation in Iraqi child theatre . the third chapter is the research procedure where the expressional procedure was employed to analyze the samples. The researcher reached several results and conclusions listed in the forth chapter also some recommendations and suggestions and lastly a list of references.